DEVELOPMENT OF SELF-REGULATION OF BEHAVIOR IN PRIMARY SCHOOL STUDENTS IN PRIMARY EDUCATION - Талипова Фарогат Рустамовна (Innovate Conferences, 2026)
This article examines the development of self-regulation in primary school students. Self-regulation is defined as a critical psychological mechanism that enables conscious management of a child's actions, emotions, and academic performance. In primary school, the development of self-regulation is particularly important, as this age period is characterized by the active development of voluntariness, responsibility, and academic motivation. This paper analyzes psychological and pedagogical approaches to developing self-regulation, revealing the role of learning activities, pedagogical support, and the educational environment in developing the regulatory skills of primary school students. The importance of goal-setting, planning, self-control, and reflection as key components of self-regulation is emphasized. It is demonstrated that the targeted use of play-based, activity-based, and student-centered teaching methods contributes to an increase in students' self-regulation. The results of this study can be used in primary education to improve the effectiveness of the educational process.
Keywords: self-regulation of behavior; primary school students; primary education; educational activities; arbitrariness of behavior; pedagogical support; personal development.